2021
DOI: 10.25259/sni_112_2021
|View full text |Cite
|
Sign up to set email alerts
|

Using smartphone-based accelerometers to gauge postoperative outcomes in patients with NPH: Implications for ambulatory monitoring

Abstract: Background: The surgical treatment of normal pressure hydrocephalus (NPH) with shunting remains controversial due to the difficulty in distinguishing such pathology from other neurological conditions that can present similarly. Thus, patients with suspected NPH should be carefully selected for surgical intervention. Historically, clinical improvement has been measured by the use of functional grades, alleviation of symptoms, and/or patient/family-member reported surveys. Such outcome analysis can be subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The applications use accelerometer and gyroscope data to assess balance and gait and to detect the freezing of gait patterns ( 30 ). The use of such technology with patients with iNPH has been reported in two patients so far ( 31 ). A recent study investigated the walking pattern of healthy subjects and patients with iNPH in a controlled and real-world environment through the use of wearable gait assessment devices ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The applications use accelerometer and gyroscope data to assess balance and gait and to detect the freezing of gait patterns ( 30 ). The use of such technology with patients with iNPH has been reported in two patients so far ( 31 ). A recent study investigated the walking pattern of healthy subjects and patients with iNPH in a controlled and real-world environment through the use of wearable gait assessment devices ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies have identified challenges in the application and variability of results while using activity-monitoring tracking data for the assessment of gait improvement in iNPH after CSF diversion surgery. 21,22 Also, in a study by Ferrari et al, there was a significant correlation between clinical variables and data from inertial sensors, 23 although paired analysis was not performed comparing the changes over time.…”
Section: Discussionmentioning
confidence: 99%